Inhibition of 14-3-3 Proteins Alters Neural Oscillations in Mice - Jones, Zachary B.; Zhang, Jiajing; Wu, Yuying; Zhou, Yi (Frontiers in Neural Circuits, 2021)
Accumulating evidence suggests that schizophrenia is a disorder of the brain’s communication, a result of functional and structural dysconnectivities. Patients with schizophrenia exhibit irregular neuronal circuit and network activity, but the causes and consequences of such activity remain largely unknown. Inhibition of 14-3-3 proteins in the mouse brain leads to the expression of multiple schizophrenia endophenotypes. Here we investigated how 14-3-3 inhibition alters neuronal network activity in the mouse hippocampus and prefrontal cortex, key brain regions implicated in schizophrenia pathophysiology. We implanted monopolar recording electrodes in these two regions to record local field potentials both at rest and during a cognitive task. Through our assessment of band power, coherence, and phase-amplitude coupling, we found that neural oscillations in the theta and gamma frequency ranges were altered as a result of 14-3-3 dysfunction. Utilizing transgenic and viral mouse models to assess the effects of chronic and acute 14-3-3 inhibition on oscillatory activities respectively, we observed several fundamental similarities and differences between the two models. We localized viral mediated 14-3-3 protein inhibition to either the hippocampus or prefrontal cortex, allowing us to assess the individual contributions of each region to the observed changes in neural oscillations. These findings identify a novel role of 14-3-3 proteins in neural oscillations that may have implications for our understanding of schizophrenia neurobiology.